Synthesis, Characterization and Biologial Evaluation of 2-amino-3-(n-cyclohexyl carboxamido)- 4,5,6,7-tetrahydrobenzo (b) Thiophine Derivatives. - Singh, Archana (International Journal of Pharmaceutical & Biological Archive, 2011)
Derivatives of 2- amino- 3- (N- cyclohexyl carboxamido)- 4,5,6,7- tetrahydrobenzo (b) thiophine were prepared and evaluated as antimicrobial. Despite finding that 2- amino- 3- (N- cyclohexyl carboxamido)- 4,5,6,7- tetrahydrobenzo (b) thiophine possess the activity on allosteric receptor as antimicrobial agents